TDLAS-based in situ diagnostics for the combustion of preheated ultra–lean dimethyl ether/air mixtures. (1st March 2020) - Nevrlý, Václav; Dostál, Michal; Klečka, Vít; Bitala, Petr; Válek, Václav; Vašinek, Michal; Blejchař, Tomáš; Suchánek, Jan; Zelinger, Zdeněk; Wild, Jan
Abstract: A combined experimental and modelling study of the structure of a laminar premixed ultra–lean ( ϕ = 0.33 ) dimethyl ether/air flame at atmospheric pressure and an elevated temperature was carried out. The work aimed to apply tunable diode laser absorption spectroscopy to the identification of various flame regimes that are relevant to the oxidation of dimethyl ether. One-dimensional calculations employing burner-stabilized flame assumptions confirmed the significance of low-temperature combustion chemistry. A stable double-flame structure was predicted using state-of-the-art chemical kinetic schemes and was revealed by the experimental observations. The feasibility of the novel experimental strategy based on the preheated flat-flame burner and scanned wavelength modulation spectroscopy was investigated in this context. The absorption features of hot water and the hydroxyl radical near 1572 nm were selected as appropriate targets for distinguishing the transition from the cool flame regime to the hot flame regime. Discrepancies in the water line position and intensities were found within the 1509 nm region.